2007
DOI: 10.1111/j.1742-7843.2007.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lycopene on Nephrotoxicity Induced by Mercuric Chloride in Rats

Abstract: Oxidative stress is an important molecular mechanism for kidney injury in mercury poisoning. We studied lycopene, a potent carotenoid found in tomatoes due to its large antioxidant properties, and also evaluated the ability of lycopene to prevent HgCl 2 nephrotoxicity. Rats were injected with HgCl 2 (0 or 5 mg/kg body weight, subcutaneously) 6 hr after lycopene administration (0, 10, 25 or 50 mg/kg by gavage) and were killed 12 hr after HgCl 2 exposure. HgCl 2 -induced inhibition of δ -aminolevulinate dehydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 34 publications
4
27
0
2
Order By: Relevance
“…3), which is due to mercury toxicity as also reported by Carmichael and Fowler (1979) and Al-Saleh et al (2005). In kidney tissue, the sign of toxicity was also observed (Figs 4 and 5 et al (2007) and Augusti et al (2007) have also reported similar changes due to mercury-induced nephrotoxicity. The high MT-I and MT-II mRNA expression levels in the liver tissues of the GNO + Hg group may be due to the oxidative stress caused by ROS generated by mercury toxicity.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…3), which is due to mercury toxicity as also reported by Carmichael and Fowler (1979) and Al-Saleh et al (2005). In kidney tissue, the sign of toxicity was also observed (Figs 4 and 5 et al (2007) and Augusti et al (2007) have also reported similar changes due to mercury-induced nephrotoxicity. The high MT-I and MT-II mRNA expression levels in the liver tissues of the GNO + Hg group may be due to the oxidative stress caused by ROS generated by mercury toxicity.…”
Section: Discussionsupporting
confidence: 60%
“…The toxicity of HgCl2 is attributed to the high affinity of Hg(II) to thiol groups owing to which it can deplete cellular GSH and damage proteins and thiol enzymes (Augusti et al, 2007). We found decreases in GSH levels in liver and kidney tissues as a result of mercury exposure (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…In conclusion, because lycopene, an antioxidant substance in the carotenoid family of compounds, can mitigate/abrogate oxidative stress (see most recent of > 200 papers on subject, i.e., Attesahin et al, 2007;Bose and Agrawal, 2007;Neyestani et al, 2007)-including that induced by mercury (Augusti et al, 2007)-it is likely that this effect is an important factor in the keratinocytes' renewed ability to establish GJIC and undergo inducible cytokine formation that had been reduced by mercury. Further studies by our research group will better clarify the mechanisms by which lycopene had the effects shown here and determine if these can be replicated with other known toxicants, particularly carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…(DA SILVA et al, 2007;PEROTTONI et al, 2004;VALENTINI et al, 2007VALENTINI et al, , 2008VALENTINI et al, , 2009. Estudos com animais mostraram inibição da atividade da mesma após a exposição ao Hg (AUGUSTI et al, 2007(AUGUSTI et al, , 2008FARINA et al, 2004;NOGUEIRA et al, 2003;VALENTINI et al, 2009) A reativação da ALA-D pode ser usada em estudos clínicos e epidemiológicos para avaliar a ação da condição oxidante crônica sobre os grupos -SH da enzima (GONÇALVES et al, 2005;GROTTO et al, 2010;VALENTINI et al, 2007VALENTINI et al, , 2008 O processo inflamatório crônico está envolvido em distúrbios que envolvem o sistema cardiovascular (LIUZZO et al, 1994, RIDKER et al, 2000. Ademais, alterações nesse sistema estão associados com a exposição ao Hg (DE MARCO et al, 2010;FILLION et al, 2006;GUALLAR et al, 2002;MOZAFFARIAN, 2009;RISSANEN et al, 2000;VIRTANEN et al, 2005).…”
Section: Discussionunclassified
“…O desequilíbrio entre antioxidantes e pró-oxidantes pode levar aos mais diversos danos celulares, desencadeando alterações progressivas em proteínas, lipídios, açúcares e DNA, reduzindo sua capacidade funcional e aumentando o risco ao desenvolvimento de doenças (BERR, 1998;FINKEL;HOLBROOK, 2000). (AUGUSTI et al, 2007(AUGUSTI et al, , 2008FARINA et al, 2004;GROTTO et al, 2010;NOGUEIRA et al, 2003;PEROTTONI et al, 2004;VALENTINI et al, 2007VALENTINI et al, , 2008). …”
Section: Estresse Oxidativo E Mehgunclassified